MODUS OPERANDI KORUPSI DALAM OTONOMI DAERAH DI INDONESIA DILEMA, TANTANGAN DAN STRATEGI ANTI KORUPSI (CORRUPTION OPERANDY MODULE IN REGIONAL AUTONOMY IN INDONESIA DILEMA, CHALLENGES AND ANTI CORRUPTION STRATEGY) - Lesmana Rian Andhika (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
The emergence of various cases of corruption that ensnared officials indicate this problem area is the overwhelming issue. Abuse of authority following the habitual threatening officials of organizing good governance, aggravate the public service, can give the effect of damaged and even more danger from corruption in the practice of prostitution. This research article would like to give you an idea of how the phenomenon of corruption practices with different modes for this happening on local governments, collusion between the legislature and the executive. The specific purpose of this research is focused on revealing of corruption with the modus operandi of classic or modern, dilemmas, challenges and strategies of anti-corruption and finding or developing the newest way in answering the question of the modus operandi of corruption. The method in this research is a library research to be able to express views critical of a variety of scientific literature and source the relevant reading for a revealed various phenomenon of corruption that occur in the implementation of the autonomous region in Indonesia. More than these studies libraries put more emphasis on the collection of information the data comes from the relevant reading materials, records, and processing data for scientific research and has a specific purpose. The results of this study revealed that the modus operandi of the more modern corruption such as the utilization of the regional Bank for depositing funds budget within a specified time that is necessary to prevent the systematic steps will narrow the space motion of corruption in local government. Keywords: Modus Operandi, Corruption, Regional Autonomy